Astaxanthin enhances LRP1‐modulated insulin sensitivity and amyloid beta clearance in an in vitro blood‐brain barrier model. (December 2021) - Babalola, Joshua Adekunle; Lang, Magdalena; George, Meekha; Stracke, Anika; Tadic, Jelena; Madeo, Frank; Lass, Achim; Leitinger, Gerd; Hutter‐Paier, Birgit; Hoefler, Gerald; Panzenboeck, Ute
Abstract: Background: Brain capillary endothelial cells (BCECs) are integral components of both the blood‐brain barrier (BBB) and the neurovascular unit (NVU). Transport across the BBB is an important mediator of beta‐amyloid (Aβ) accumulation in the brain and a contributing factor in the pathogenesis of Alzheimer's disease (AD). One of the receptors responsible for the transport of Aβ through the BBB is the low‐density lipoprotein receptor‐related protein 1 (LRP1). In addition, the development of AD and diabetes share many pathophysiological features including defective insulin signalling, impaired glucose metabolism, and cognitive decline. LRP1 is known to modulate insulin signalling by forming a dimer with insulin receptor beta when stimulated using insulin. Furthermore, LRP1 expression at the BBB is reduced during normal aging and in AD. Hence, we hypothesize that LRP1 activity in BCEC can be modulated using astaxanthin to improve Aβ clearance and insulin‐mediated signalling at the BBB. Method: By using the established in vitro porcine brain capillary endothelial cell (pBCEC) model of the BBB, we analyzed the effects of astaxanthin on LRP1 expression, Aβ clearance, insulin‐mediated signalling and other systemic dysfunctions associated with AD at the protein and mRNA level. We also examined the ultra‐structures by electron microscopy. Result: pBCECs showed enhanced expression of LRP1 when treated with astaxanthin. We further observed improved insulin sensitivity when cells pre‐incubated with astaxanthin were treated with Aβ1‐40, Aβ1‐42 and Aβ1‐40 + Aβ1‐42 and insulin and further stimulated with insulin (10 nM). Increased expression of LRP1, Aβ‐degrading enzymes, as well as autophagy and insulin signalling markers were observed when pBCECs pre‐incubated with astaxanthin were further treated with amyloid beta peptides. Conclusion: Our results suggest that increased LRP1 expression by astaxanthin enhances insulin sensitivity, autophagy induction and improves Aβ degradation. Astaxanthin could thus be a promising therapeutic candidate for Alzheimer's disease.